Fast 3-D Imaging of Brain Organoids With a New Single-Objective Planar-Illumination Two-Photon Microscope - Irina Rakotoson; Irina Rakotoson; Irina Rakotoson; Irina Rakotoson; Brigitte Delhomme; Brigitte Delhomme; Brigitte Delhomme; Philippe Djian; Philippe Djian; Philippe Djian; Andreas Deeg; Maia Brunstein; et al. (Frontiers Media S.A., 2019)
Human inducible pluripotent stem cells (hiPSCs) hold a large potential for disease modeling. hiPSC-derived human astrocyte and neuronal cultures permit investigations of neural signaling pathways with subcellular resolution. Combinatorial cultures, and three-dimensional (3-D) embryonic bodies (EBs) enlarge the scope of investigations to multi-cellular phenomena. The highest level of complexity, brain organoids that-in many aspects-recapitulate anatomical and functional features of the developing brain permit the study of developmental and morphological aspects of human disease. An ideal microscope for 3-D tissue imaging at these different scales would combine features from both confocal laser-scanning and light-sheet microscopes: a micrometric optical sectioning capacity and sub-micrometric spatial resolution, a large field of view and high frame rate, and a low degree of invasiveness, i.e., ideally, a better photon efficiency than that of a confocal microscope. In the present work, we describe such an instrument that uses planar two-photon (2P) excitation. Its particularity is that-unlike two- or three-lens light-sheet microscopes-it uses a single, low-magnification, high-numerical aperture objective for the generation and scanning of a virtual light sheet. The microscope builds on a modified Nipkow-Petráň spinning-disk scheme for achieving wide-field excitation. However, unlike the Yokogawa design that uses a tandem disk, our concept combines micro lenses, dichroic mirrors and detection pinholes on a single disk. This new design, advantageous for 2P excitation, circumvents problems arising with the tandem disk from the large wavelength difference between the infrared excitation light and visible fluorescence. 2P fluorescence excited by the light sheet is collected with the same objective and imaged onto a fast sCMOS camera. We demonstrate 3-D imaging of TO-PRO3-stained EBs and of brain organoids, uncleared and after rapid partial transparisation with triethanolamine formamide (RTF) and we compare the performance of our instrument to that of a confocal laser-scanning microscope (CLSM) having a similar numerical aperture. Our large-field 2P-spinning disk microscope permits one order of magnitude faster imaging, affords less photobleaching and permits better depth penetration than a confocal microscope with similar spatial resolution.